Production and analysis of composite nanofiber and heat applied nanofiber - (:unkn) unknown (My University, 2012)
Bu çalışmada, iki farklı nanolif uygulaması denenmiştir. Birinci uygulamada, çevresel sıcaklıkta solvent tekniğiyle nanolif elde edilemeyen Maleik Anhidrid graftlı Polipropilenden (MAH PP) nanolif elde edilmiştir. Çözelti sıcaklığının nanolif üretilebilirliğine etkisi incelenmiştir. Sonuçta 70°C altında nanolif üretilemediği gözlenmiştir. Çözelti sıcaklığı 100°C civarında iken bead yapısında artış görülmüştür. Yüksek sıcaklığın viskoziteyi düşürmesi bead oluşumunu arttırmıştır. Diğer uygulamada ise selüloz nanowhiskers (CNW) ile beraber elastomeric polimerden (Polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene graft-maleic anhydride) (SEBS-g-MA) kompozit nanolif üretilmiştir. Besleme hızı ve çözeltideki su miktarının lif yapısına olan etkisi incelenmiştir. Su miktarındaki artışın lif yapısında deformasyona neden olduğu, besleme hızındaki düşüşün ise daha ince lif yapısı oluşumuna katkıda bulunduğu gözlenmiştir.

In this study, two different applications related with nanofiber production have been studied. In one application, nanofiber was obtained from Maleic Anhydrite grafted Polypropylene (MAH PP) that it is not possible to produce nanofiber at the environmental temperature by solvent technique. The effect of the temperature of polymer solvent on nanofiber producibility has been investigated. It has been seen that it is not possible to produce nano fiber by o o solvent below 70°C The bead on the nanofiber increases when solution temperature is around 100°C Bead formation may be due to lower viscosity resulted from higher temperature. In the other application, elastomeric polymer (Polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene graft-maleic anhydride) (SEBS-g-MA) together with cellulose nanowhiskers (CNW) was used to produce composite nanofiber. The effect of feed rate and also the amount of water content on properties of composite nanofiber have been investigated. It has been seen that an increase of water content results to deformation of nanofiber morphology and decrease of feeding rate results to thinner fiber.
Kompozit nanolif ve ısı uygulanmış nanoliflerin üretim ve analizi